Recipes for Remaking: Exploring Transience and Permanence in the Everyday Practices of Eating, Sharing and Cooking Food - Torr, Matthew (Auckland University of Technology, 2023)
Recipes for re-making is a practice-led research project that explores ways of re-making spaces that are associated with food, through the assemblage of abstract ceramic objects. Eating is an act both banal and extraordinary – we eat out of necessity, but also to mark social occasions, celebrate moments of company or as forms of pleasure. It is an act of the everyday and it is my own observations around the everyday acts of eating, sharing and preparing food that form the basis of this research. I am interested in the connection between eating and the spatial environments in which this action occurs. Through a reflective, deconstructive approach, I identify and isolate elements from memory-fragments and preserve them as ceramic objects. Using recipe making as a key method for exploration, I use the culinary terms Ingredients and Methods to document the making of ceramic objects. These ceramic objects then themselves become the ingredients in the recreation of spatio-temporal foodscapes through assemblages of sensory and tactile engagements with texture, repetition and material. Through using recipe making as both a method for documentation and for re-making remembered spaces and experiences, the project asks if there is an opportunity to re-engage with these temporal spaces of past food memories through object making and novel assemblages of non-representational ceramic objects.